ANALISIS FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA BERWIRAUSAHA DENGAN METODE ELECTRE II - Laila Safitri; Poningsih Poningsih; Jalaluddin Jalaluddin (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
This study aims to determine the most fundamental factors in influencing student interest in entrepreneurship at Pematangsianta. The method used in decision making is the ELECTRE II method. Which will be implemented into vb net 2010. Based on the research results obtained by Capital (A3) as rank 1, It is hoped that this research will provide input and convenience to the education parties in knowing what fundamental factors influence student interest in entrepreneurship.Keywords: Students, Interests, Entrepreneurship, SPK, Electre II.